2021
DOI: 10.21801/ppcrj.2021.73.4
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulatory effects of Transcranial Pulsed Current Stimulation (tPCS) in Fibromyalgia: protocol for a double-blinded, sham-controlled, randomized clinical trial

Abstract: Fibromyalgia (FM) is a functional syndrome characterized by musculoskeletal, diffuse and persistent (> 3 months) chronic pain, that is also characterized by sleep disturbances, fatigue, humor changes and cognitive and psychological changes. Transcranial Pulsed Current Stimulation (tPCS) is a new Transcranial Electrical Stimulation (tES) that has been studied as a treatment option for chronic pain and neurological conditions . Studies have shown that tPCS is capable of pain and cognitive modulation; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 12 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…These studies demonstrated the significant positive effect of tPCS on a number of clinical conditions, including consciousness after brain injury (Barra et al., 2022), spasticity and movement disorders in patients with spinal cord injury (SCI) (Iddings et al., 2019, 2021; Liu et al., 2021), pain and cognition in fibromyalgia (Castro et al., 2021), cognitive dysfunction in schizophrenia (Singh et al., 2019), spastic cerebral palsy (SCP) (Thibaut, Russo, Morales‐Quezada, et al., 2017), and balance and movement in Parkinson's disease (Alon et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies demonstrated the significant positive effect of tPCS on a number of clinical conditions, including consciousness after brain injury (Barra et al., 2022), spasticity and movement disorders in patients with spinal cord injury (SCI) (Iddings et al., 2019, 2021; Liu et al., 2021), pain and cognition in fibromyalgia (Castro et al., 2021), cognitive dysfunction in schizophrenia (Singh et al., 2019), spastic cerebral palsy (SCP) (Thibaut, Russo, Morales‐Quezada, et al., 2017), and balance and movement in Parkinson's disease (Alon et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Since women's menstrual cycle may potentially affect the size of CSE induced by tPCS, some studies have exclusively recruited male participants 21–25 years old (Saito et al., 2019, 2022) or college athletes (Shen et al., 2022; Wu et al., 2022a, 2022b). In studies with patient populations, the sample sizes ranged from 6 to 70 participants between the ages of 2 and 85 (Alon et al., 2011; Barra et al., 2022; Castro et al., 2021; Iddings et al., 2019, 2021; Liu et al., 2021; Singh et al., 2019; Thibaut, Russo, Hurtado‐Puerto, et al., 2017). All these studies recruited both male and female participants, except one, which only recruited females with fibromyalgia (Castro et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations